2019
DOI: 10.1002/bjs.11171
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of outcomes after total neoadjuvant therapy for locally advanced rectal cancer

Abstract: Background Advances in surgical technique and the development of combined‐modality therapy have led to significantly improved local control in rectal cancer. Distant failure rates however, remain high, ranging between 20 and 30 per cent. Additional systemic chemotherapy in the preoperative period has been proposed as a means of eradicating subclinical micrometastases and improving long‐term survival. The purpose of this systematic review was to evaluate the current evidence regarding induction chemotherapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 48 publications
1
60
0
1
Order By: Relevance
“…Furthermore, EORTC 22941 and FFCD 9203 tested different combinations of RT and chemotherapy and demonstrated that 5-FU-based chemotherapy combined with RT has the best results [29,30]. In addition, several studies demonstrated that total neoadjuvant therapy (TNT), in which chemoradiation and chemotherapy are administered prior to surgery, is a viable treatment for LARC [31][32][33]. In our study, the majority of patients who underwent neoadjuvant RT (98.0%) and adjuvant RT (91.5%), also received chemotherapy.…”
Section: Neoadjuvant Rt Improves Os For T3/4n + M0 Rectal Cancer Patimentioning
confidence: 99%
“…Furthermore, EORTC 22941 and FFCD 9203 tested different combinations of RT and chemotherapy and demonstrated that 5-FU-based chemotherapy combined with RT has the best results [29,30]. In addition, several studies demonstrated that total neoadjuvant therapy (TNT), in which chemoradiation and chemotherapy are administered prior to surgery, is a viable treatment for LARC [31][32][33]. In our study, the majority of patients who underwent neoadjuvant RT (98.0%) and adjuvant RT (91.5%), also received chemotherapy.…”
Section: Neoadjuvant Rt Improves Os For T3/4n + M0 Rectal Cancer Patimentioning
confidence: 99%
“…However, there are many patients whose outcomes do not match those typical for their tumor stage and accurate prognostic information for individual patients can be difficult to estimate owing to the heterogeneous nature of the disease. Many new combinations of chemotherapy with radiotherapy, including total neoadjuvant therapy (TNT) with targeted therapies that aim to diminish toxicity and increase survival, are being evaluated in clinical trials (10,11). Despite these advances, local recurrence and distant metastasis remain an issue, with one-third of LARC patients dying within 5 years of initial treatment (10).…”
Section: Introductionmentioning
confidence: 99%
“…The management of rectal cancer is constantly evolving. Some of the recent changes in rectal cancer management are directed toward the sequencing of multidisciplinary treatment including the use of total neoadjuvant therapy which incorporates neoadjuvant radiation and neoadjuvant chemotherapy before surgery 1,2 . Moreover, the concept of overtreatment in rectal cancer has lead to investigations on the selective use of radiation and as well as the concept of nonoperative management of rectal cancer 3‐5 .…”
Section: Introductionmentioning
confidence: 99%